Analisis Kebutuhan Bahan Bakar Terbang Jelajah Pesawat Cessna 172 Berdasarkan Variasi Kecepatan - Madjid, Aldien Galistia Maharani; Mufti Arifin; Ade Julizar (FTK UNSURYA, 2025)
This research investigates the correlation between cruise speed, fuel consumption, and propeller efficiency in the Cessna 172 aircraft during actual flight conditions. The study involved five test flights conducted at different cruise speeds: 87.7, 90.8, 98.4, 105.3, and 113.5 knots, each flown over 100 nautical miles at 5,000 feet altitude. Fuel consumption was calculated by comparing initial and final fuel levels, revealing that actual usage consistently exceeded the Pilot Operating Handbook (POH) estimates. For instance, at 87.7 knots, actual fuel consumption was 39.61 L/hr, significantly higher than the POH value of 21.26 L/hr. Propeller efficiency peaked at lower speeds (0.828 at 87.7 knots) and declined at higher speeds (0.628 at 113.5 knots), indicating reduced aerodynamic performance. These findings underscore the importance of selecting optimal cruise speeds to enhance fuel efficiency, reduce operational costs, and extend aircraft lifespan. The study provides practical insights for pilots and operators aiming to optimize light aircraft performance in real-world operations